1994
DOI: 10.1016/0741-5214(94)90003-5
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of popliteal aneurysms

Abstract: Intraarterial thrombolysis is of value in restoring the distal run off before bypass in PA presenting as acute limb-threatening ischemia. However, the results do not justify an expectant policy for asymptomatic aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
2
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 15 publications
3
107
2
3
Order By: Relevance
“…However, size does relate to symptoms. 20 We found 10 that the median diameter of asymptomatic popliteal aneurysms was 2.0 cm (range, 1.5-4.8 cm). This compared with 3 cm (range, 1.4-4.6 cm) for popliteal aneurysms producing acute ischaemia and 3.45 cm (range, 3.0-5.6 cm) for those producing compression ( P = 0.0021 and P = 0.0045, respectively).…”
Section: Sizementioning
confidence: 98%
See 1 more Smart Citation
“…However, size does relate to symptoms. 20 We found 10 that the median diameter of asymptomatic popliteal aneurysms was 2.0 cm (range, 1.5-4.8 cm). This compared with 3 cm (range, 1.4-4.6 cm) for popliteal aneurysms producing acute ischaemia and 3.45 cm (range, 3.0-5.6 cm) for those producing compression ( P = 0.0021 and P = 0.0045, respectively).…”
Section: Sizementioning
confidence: 98%
“…20 One study has shown a greater risk of complications developing in those popliteal aneurysms associated with absent distal pulses. 21 It is postulated that embolisation from the aneurysm can gradually occlude runoff.…”
Section: Thrombus Within Popliteal Aneurysm and Run-offmentioning
confidence: 99%
“…Thrombolysis has been shown to improve outcome in the emergency treatment of patients with acute thrombosis 13 by improving run off.…”
Section: Discussionmentioning
confidence: 99%
“…6 The most common surgical technique used for the repair of a PAA is the medial approach with proximal and distal aneurysms ligation, combined with autologous vein or polytetrafluoroethylene (PTFE) bypass grafting. 7 However, this technique does not exclude side branches with their origin in the PAA, which may be responsible for continued retrograde perfusion in the ligated aneurysm, which can eventually lead to aneurysm enlargement. 5,8 An alternative technique is the posterior approach.…”
Section: Introductionmentioning
confidence: 99%